The political and religious system according to Arif Al-Saadi - Al shadood, Hayder Abed Alkhadim; seydedi, Dr. seyed hosein (Thi Qar Arts Journal, 2024)
It is worth giving our venerable poets academic and research attention, especially the poet Arif Al-Saadi, because he is creative and possesses a conscious text. We have chosen a portion of his huge works, and the choice fell on some of his poems, which contain within them an apparent and implicit political tone, as his poetry was a reflection of reality of the Iraqi people, being a renewed poet in contemporary Iraqi poetry, and one of the signatories of the most prominent modernist phenomenon in Arabic literature, which is the so-called (poetry), became the official spokesman for the people. This research is concerned with studying the systematic dominant of the expressive formulation of the axis of politics according to what the systematic study started from, which requires creative communication. The inclinations and orientations of the creator became effective in monitoring the meaning, in light of their typicality, far from the possibility of change, and - perhaps this is unfamiliar - in terms of the occurrence of the political and religious pattern, and the extent to which it has the intention, and the poetic mentality of Arif Al-Saadi, through its aesthetics, and in juxtaposition with the grammatical pattern, and he is trying to create a changeable action, keeping pace with the logic of building the human being and the state in the light of human thought, and social justice that has been absent from the ruling authority that he poured his lash of torment upon her.